Exploring individual and organizational contributors to workplace deviant behavior - D. Daryono; R. Gunawan; U. Udin (International Journal of Human Capital in Urban Management)
BACKGROUND AND OBJECTIVES: Workplace deviant behavior, as a manifestation of employee conduct, can exert adverse effects on an organization, posing challenges to its overall functioning and well-being. Understanding the underlying mechanism is essential in offering insights to enhance risk mitigation and promote a positive organizational culture for sustained success. Therefore, the study on workplace deviant behavior is important because it addresses both practical and theoretical concerns crucial for organizations' functioning and success. Additionally, it helps in understanding the dynamics of employee behavior, developing effective management strategies, and promoting a productive and ethical workplace environment. The novelty and originality of this research lie in its integration of these three variables to understand their combined impact on workplace deviant behavior. This approach provides a more detailed and nuanced understanding of the factors contributing to deviant behavior, allowing for more effective mitigation strategies.METHODS: This study aims to examine the impact of employee personality, organizational culture, and perceived organizational support on workplace deviant behavior among 370 employees at Human Development Agencies in Indonesia. Data were collected using questionnaires and analyzed using IBM SPSS version 26.FINDINGS: The results showed a significant negative correlation between employee personality traits, such as extraversion (t-value = -2.400, ρ-value = 0.019, ρ < 0.05) and agreeableness (t-value = -2.170, ρ-value = 0.034, ρ < 0.05), and organizational culture (t-value = -2.386, ρ-value = 0.020, ρ < 0.05). However, perceived organizational support only moderates organizational culture's influence on workplace deviant behavior, not employee personality traits. The study suggests strategies to prevent and mitigate its negative effects on organizations.CONCLUSION: The study recommends the implementation of conducive policies and practices to efficiently handle these behaviors. Moreover, this study enhances comprehension of workplace deviant behavior and provides pragmatic suggestions for effectively managing and averting such conduct within organizations. This highlights the significance of creating supportive policies and practices that specifically address organizational culture and support mechanisms to effectively reduce workplace deviant behavior.